2021
DOI: 10.3389/fneur.2021.697974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pregnancy in Multiple Sclerosis and Impact of Disease-Modifying Therapies

Abstract: Purpose of this Review: This article is a systematic review on the influence pregnancy has on multiple sclerosis and the resulting impact of disease-modifying therapies.Findings: Multiple sclerosis predominantly affects young women with a clinical onset most often during the child-bearing age. The impact of multiple sclerosis and disease-modifying therapies on fertility, pregnancy, fetal outcome, and breastfeeding is a pivotal topic when it comes to clinical practice. The introduction of disease-modifying ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 144 publications
(190 reference statements)
1
17
0
3
Order By: Relevance
“…The introduction of DMT significantly changed pregnancy planning in women with MS. One of the strongest risk factors for postpartum relapse is untreated MS two years before conception. IFNβ and GA are allowed during pregnancy, while IFNβ beta is allowed during breastfeeding as well ( 17 ).…”
Section: Recommendations For Initiation Of Treatment Of Pwms With Pla...mentioning
confidence: 99%
“…The introduction of DMT significantly changed pregnancy planning in women with MS. One of the strongest risk factors for postpartum relapse is untreated MS two years before conception. IFNβ and GA are allowed during pregnancy, while IFNβ beta is allowed during breastfeeding as well ( 17 ).…”
Section: Recommendations For Initiation Of Treatment Of Pwms With Pla...mentioning
confidence: 99%
“…Alemtuzumab is another monoclonal antibody with a molecular weight of 150 kDa, a half-life of 4-5 days, and complete elimination in 30 days that interacts with the CD52 surface receptor on cells [61]. Premature labor, hypertension, low birth weight, and neurocognitive impairment are some fetal concerns associated with using alemtuzumab during pregnancy [62,63].…”
Section: Alemtuzumabmentioning
confidence: 99%
“…In contrast to monoclonal antibodies, alemtuzumab does not cross the placental during the first trimester. Nevertheless, it recommends using effective contraception for women under alemtuzumab therapy for at least four months after completion of treatment [61]. Oh et al indicated that among 264 pregnancies exposed to alemtuzumab, 67% were live births without anomalies, 22% spontaneous abortions, 11% elective abortions, and one stillbirth [61].…”
Section: Alemtuzumabmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, studies have shown a risk of hematological disorders such as anemia and thrombocytopenia in the newborns of mothers exposed to NAT during their third trimester [6]. However, these hematological alterations were back to normal within four months after birth in most patients, without much intervention [7].…”
Section: Introductionmentioning
confidence: 99%